Nage libre : la lettrre d'info des adhérents de Paris Aquatique. (Paris : Paris Aquatique, 1996)
Fonds Suzan Daniel (FSD)
Periodiciteit: maandelijks
Redactie: 3 rue Guillaumot, 75012 Paris
Frans
Periodiek